Moral judgment as a pivotal modulator in entrepreneurial cognition frameworks - Rizal, Ach. Syaiful; Ali Alnajar, Ali Elazumi; Permadi, Edo Galih (Manajemen dan Bisnis, 2024)
This study aims to reconstruct the adoption of the theory of planned behaviour for predicting entrepreneurial intentions by examining moral judgement as an intervening variable. This study is significant in the present times since there is flawed reasoning when analysing entrepreneurial intentions. Most people believe that entrepreneurial intention is a manifestation of social aspects or favourable or unfavourable evaluation of the behaviour of interest. As such, they formulate that those aspects directly affect entrepreneurial intentions. Within the current study, our analyses do not provide strong empirical evidence for such claims. It is documented that moral judgment becomes a mediator for the use of social aspects to predict entrepreneurial intentions. Then, this study also found that moral judgment is the best and closest predictor of entrepreneurial intentions. Therefore, our study proposes different directions to understand and predict entrepreneurial intentions.